Relações materno-filiais e sua influência no peso pré-desmama de animais Nelore da Bahia - Souza, E. A.; Andrea, M. V.; Santos, C. S.; Costa, M. J. R. Paranhos da [UNESP]; Bittencourt, T. C. B. S. C.; Marcondes, C. R. (SciELO Espana/Repisalud, 2009)
The aim of this study was to investigate the maternal-offspring relationships in the bovine breeds Nellore PO (Pure Breed) and Nellore CL (Cara Limpa) in Bahia State. The genetic composition of breeds did not affect LP (latency time to stand); this variable showed mean values of 71 min and 52 min, respectively, for Nellore PO and Nellore CL. The variable LPTM (latency time to begin suckling after standing) was significantly higher for Nellore PO (mean values of 39 min) tham for Nellore CL (18 min). The variable TCC (time in contact with the calf) was classified as class 4 (60 to 80% of the time was spent with the calves). The P120 (weight at 120 days) had mean values of 122.3 kg and 122.7 kg respectively, for Nellore PO and Nellore CL. In conclusion, the maternal-offspring behaviour had little influence of the genetic composition of the breeds. These results suggest that more studies are necessary to define technological parameters for cattle raising in Bahia State.
Mother-offspring relations and its influence in preweaning weight in Nellore animals of the Bahia
Keywords: Animal Behavior; Weaning; Zebu; Animalia; Bos; Bos indicus; Bovinae